How The World Works - Chomsky, Noam; Edited by Naiman, Arthur (London Hamish Hamilton, 2011)
"With exceptional clarity and power of argument, Noam Chomsky lays bare as no one else can the realities of contemporary geopolitics. Divided into four sections and originally published in the US as individual short books which have collectively sold over half a million copies, How the World Works is a collection of speeches and interviews with Chomsky by David Barsamian, edited by Arthur Naiman. It includes What Uncle Sam Really Wants, about US foreign policy; The Prosperous Few and the Restless Many, about the new global economy, food, Third World 'economic miracles' and the roots of racism; Secrets, Lies and Democracy, about the US, the CIA, religious fundamentalism, global inequality and the coming eco-catastrophe; and The Common Good, about equality, freedom, the media, the myth of Third World debt and manufacturing dissent"--Back cover.
Include Index
Keywords: United States -- International economic relations -- Diplomatic relations